2018
DOI: 10.1038/s41467-018-05462-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile transformation of imine covalent organic frameworks into ultrastable crystalline porous aromatic frameworks

Abstract: The growing interest in two-dimensional imine-based covalent organic frameworks (COFs) is inspired by their crystalline porous structures and the potential for extensive π-electron delocalization. The intrinsic reversibility and strong polarization of imine linkages, however, leads to insufficient chemical stability and optoelectronic properties. Developing COFs with improved robustness and π-delocalization is highly desirable but remains an unsettled challenge. Here we report a facile strategy that transforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
298
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(325 citation statements)
references
References 44 publications
(36 reference statements)
11
298
0
Order By: Relevance
“…The particle size of both F68@SS‐COFs ( Figure A) and F68@n‐COFs (Figure S2A, Supporting Information) almost remained the original size without precipitation or phase separation after incubation in the weak acidic environment for 48 h. Their stability may be due to the benefit of PEGylated shell. In addition, some previous studies have demonstrated that the imine‐based COFs, at least for a time period, are relatively stable under weak acidic condition . However, F68@SS‐COFs possessed a disulfide‐rich COFs core in the internal space and thus F68@SS‐COFs are expected to be able to disintegrate in the presence of GSH.…”
Section: Methodsmentioning
confidence: 98%
“…The particle size of both F68@SS‐COFs ( Figure A) and F68@n‐COFs (Figure S2A, Supporting Information) almost remained the original size without precipitation or phase separation after incubation in the weak acidic environment for 48 h. Their stability may be due to the benefit of PEGylated shell. In addition, some previous studies have demonstrated that the imine‐based COFs, at least for a time period, are relatively stable under weak acidic condition . However, F68@SS‐COFs possessed a disulfide‐rich COFs core in the internal space and thus F68@SS‐COFs are expected to be able to disintegrate in the presence of GSH.…”
Section: Methodsmentioning
confidence: 98%
“…To obtain a crystalline product in continuously linked molecular system, this reversible covalent bond formation is important because it allows continuous covalent bond formation/deformation process that is essential to obtain highly symmetric, stable and homogenous products 21 . Reversibility is especially important in the Schiff's base reaction [25][26][27] , because amorphous or poorly crystalline materials are easily observed in polymers such as aza-CMP that containing imines 13,28 . The presence of water and the pH of precursor solution are important factors to obtain crystalline imine-based COF by an efficient reversible imine-condensation reaction 20 .…”
mentioning
confidence: 99%
“…Despite the fact that the extended π‐conjugation can propagate through the ‐N=C‐ double bonds in the Schiff base structure, the imine‐linkage displays relatively poor stability and weak electron delocalization. To overcome this limitation, researchers have been actively exploring new reactions to construct fully conjugated COFs with an optimal electron delocalization . However, examples of fully conjugated imine‐free COFs with sp 2 ‐carbon double bond structures are still rare because it is extremely difficult to form ‐C=C‐ bonds via reversible coupling reactions and simultaneously gain the desired conjugation as well as the refined crystallinity within the COF structure.…”
Section: Methodsmentioning
confidence: 99%